Reusable melanin-based biosorbents for efficient methylene blue removal: the new frontier of fungi-inspired allomelanin coatings for sustainable water remediation processes. (March 2023) - Lino, V.; Castaldo, R.; Gentile, G.; Manini, P.
Abstract: The impact of water pollution caused by industrial wastes on our society prompted the urgent search for efficient remediation processes. Moved by the increasing interest in this research field, we report herein on the design and fabrication of an innovative water filtering device based on a nylon membrane coated with a synthetic melanin polymer inspired by fungal allomelanins and generated via the oxidative polymerization of 1, 8-dihydroxynaphthalene. The melanin coating, obtained via the straightforward and low-cost ammonia induced solid state polymerization technique, proved to be highly stable with no evidence of debonding phenomena, did not alter the porous structure of the nylon filter and its flow rate and induced a slight but appreciable improvement of its tensile properties. The adsorbing performances of the melanin coated membrane were tested toward the azo dye methylene blue both in batch and in-flow conditions and compared with those of the synthetic melanin polymer as a bulk. The data revealed that the adsorption process: a) fits quite well with the Langmuir isotherm model, suggesting a monolayer adsorption on a surface with homogeneous sites, with a maximum adsorption capacity of 262 mg/g; b) is a favourable, exothermic and spontaneous process; c) is governed by a pseudo-second order kinetics. The in-flow experiments revealed the high efficiency of the filtering membrane in removing MB up to 99%; moreover, tests carried out to assess the regeneration and reuse of the membrane showed that the methylene blue removal efficiency was not affected up to seven adsorbing/desorbing cycles. Graphical abstract: Image 1